Synthesis and Anesthetic Activity of Some Mannich Bases of p-Dimethylamino Benzylidene Acetanilide - Kalirajan, R.; Jubie, S.; Gowramma, B.; Suresh, B. (Asian Journal of Chemistry, 2010)
Some Mannich bases of p-dimethylamino benzylidine acetanilide are synthesized. The synthesized compounds have been characterized by IR and 1H NMR analysis. An attempt to determine the hydrophobic parameter (partition coefficient) is also established. All the test compounds have been screened for their local anaesthetic activity by Sollmann method.